UJI DAYA HAMBAT PERTUMBUHAN BAKTERI GRAM POSITIF DAN NEGATIF DARI PRODUK BIOTEKNOLOGI FARMASI DALAM BENTUK FORMULASI DAN SEDIAAN SABUN CUCI PIRING GEL KOMBUCHA BUNGA TELANG (Clitoria ternatea L) - Firman Rezaldi; Rustini Rustini; Ayu Safitri; Siska Dwi Anggraeni; Aris Ma'ruf; Eman Eman; Maya Puspitasari (AGRIBIOS, 2023)
Dishwashing gel soap made from telang flower kombucha fermented solution has the potential to inhibit the growth of gram-positive and negative bacteria. Gram-positive and negative bacteria that have been successfully inhibited by gel dish soap made from an active ingredient of telang flower kombucha fermented solution include Staphylococcus aureus, Staphylococcus epidermidis, Pseudomonas aeruginosa, and Escherichia coli. This research is an experimental laboratory, namely by providing dishwashing soap that has been circulating in the market as a positive control. Making a gel hand washing soap base with an active ingredient of telang flower kombucha fermented solution at a sugar concentration of 20%, 30%, and 40% which was tested against the four test bacteria consisting of two gram-positive bacteria and 2 gram-negative bacteria using disc diffusion. The data analysis used was one-way ANOVA where the resulting P value was less than 0.05 and it can be concluded that the telang flower kombucha gel dish soap at a concentration of 40% based on further analysis in the form of a post hoc test, which is significantly different from the kombucha gel dish soap butterfly pea flower at concentrations of 20% and 30% inhibited the growth of the four test bacteria but was not significantly different from the dishwashing soap on the market as a positive control. The formulation and preparation of telang flower kombucha gel dish soap at a concentration of 40% was the best concentration in inhibiting the growth of the four test bacteria compared to concentrations of 20% and 30% and even the two comparison dish soaps.